Morphological variation of two common sea grapes (Caulerpa lentillifera and Caulerpa racemosa) from selected regions in the Philippines - Jeremaiah Estrada; NONNATUS S. BAUTISTA; MARIBEL L. DIONISIO-SESE (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Estrada JL, Bautista NS, Dionisio-Sese ML. 2020. Morphological variation of two common sea grapes (Caulerpa lentillifera and Caulerpa racemosa) from selected regions in the Philippines. Biodiversitas 21: 1823-1832. Seagrapes, locally known in the Philippines as “lato” or “ar-arusip”, are economically important macroalgae belonging to the edible species of the genus Caulerpa. This study characterized and compared distinct populations of sea grapes from selected regions in the Philippines and described the influence of physicochemical parameters of seawater on their morphology. Morphometric, cluster and principal component analyses showed that morphological plasticity exists in sea grapes species (Caulerpa lentillifera and Caulerpa racemosa) found in different sites in the Philippines. These are evident in morphometric parameters namely, assimilator height, space between assimilators, ramulus diameter and number of rhizoids on stolon wherein significant differences were found. This evident morphological plasticity was analyzed in relation to physicochemical parameters of the seawater. Assimilator height of C. racemosa is significantly associated and highly influenced by water depth, salinity, temperature and dissolved oxygen whereas for C. lentillifera depth and salinity are the significant influencing factors. Highest assimilator height of sea grapes was found in Coron and Culion in Palawan due to higher salinity and temperature while in Mactan, Cebu, it is primarily attributed to lower depth and higher salinity values.